Low-carbon, environment-friendly, ultrahigh-filled wood flour/polyethylene composites: Effects of wood flour content and compatibilizer on mechanical properties, creep resistance, and rheological behavior - Haitao Fu; Jianxiu Hao; Mengyuan Dun; Ligang Zhang; Haigang Wang; Shujin Kan (Journal of Materials Research and Technology)
Increasing the amount of cheap and renewable wood flour (WF) in traditional wood–plastic composites (WPCs) can effectively enhance the cost performance and competitiveness of WPCs. This strategy aligns with global goals for sustainable and efficient resource use and carbon neutrality. In this study, ultrahigh-filled WF–polyethylene composites (UWFPEs, WF content >70 wt %) were prepared using maleic anhydride grafted polyethylene (MAPE) as an interface compatibilizer through hot pressing. Increasing the WF content can raise the internal energy consumption of the system under dynamic conditions, weaken water absorption resistance, and reduce melt fluidity, while also improving the creep resistance of the system. The MAPE-compatibilized UWFPEs exhibited high interfacial bond strength, significantly enhancing mechanical strength. When the WF content was 80 %, the bending and tensile strengths increased by 137.7 % and 152.1 %, respectively. When the WF content reached 90 %, the bending and tensile moduli further increased by 28.9 % and 22.1 %, respectively. The effective interfacial combination and improved uniformity of the architecture significantly enhanced the water resistance, dimensional stability, and creep resistance of UWFPEs. The solid-like properties of the UWFPEs were demonstrated using frequency scanning tests conducted at a strain of 0.01 %. The experimental results of this study provide reliable theoretical guidance for the practical production and application of UWFPEs.